Pengaruh Tingkat Pendidikan Formal Orang Tua terhadap Prestasi Belajar Mahasiswa Program Studi Bimbingan dan Konseling IKIP-PGRI Pontianak Tahun Akademik 2014/2015 - Eli Trisnowati (Jurnal Konseling dan Pendidikan, 2017)
This study uses fieldwork (Field Research), with a population of 150 students / i Prodi Counseling third semester of the academic year 2014/2015, which was divided into two groups: the experimental group (students who are high school level of education their parents / S1) totaled 30 people, and the control group (students whose parents education level SD) numbered 30 people. The results showed that no significant relationship between the level of formal education of parents on student achievement guidance and counseling courses Teachers' Training College PGRI Pontianak. This is shown by the price of "t" arithmetic (0.487) is less than the price of "t" of criticism, both at the 5% significance level (2.01) as well as on the significance of 1% (2.68). This means the hypothesis Alternative (Ha) rejected that there is significant between formal education level of parents on student achievement, and on the contrary hypothesis Nil (Ho) filed unacceptable that no significant relationship between the level of formal education of parents on achievement student learning. So it can be concluded that the level of education among students high school parents with a college education level of parents SD no difference in academic achievement.